Critical factors in implementing the Balanced Scorecard-BSC - Moreira, Fábio Augusto de Lucca (2012)
Several issues can be raised regarding the critical factors for implementing management models such as the Balanced Scorecard (BSC). The success demands the understanding of the model by the implementation team and the workers involved. The entertainment industry, to which the Beach Park Hotel and Tourism, presents peculiarities that make the implementation of a management model a bigger challenge, and a segment that tends to grow at a rate of 10, 6% per year until 2016. Focusing the organization and context, this study aims to identify the critical factors of implementation of the BSC, through a case study, descriptive. The results showed the following critical factors for the implementation of the BSC: the absence of a culture of strategic planning, the complexity of the business and project, the history of a management style centralized and authoritarian, the centralization of the BSC at the top, restriction of management time to devote to the project; the absence of an information system, to support the project; not performing training and the lack of external consultants. In promoting organizational change, lacked adequate involvement of the leadership and and the support of the management of the dome. In successful cases, the history of management-oriented learning serves as the basis for a proper definition of the critical needs of the organization, and defining the appropriate indicators, factors that, in the case in focus, proved absent in a company without culture of planning.